THE CORRELATION BETWEEN TEACHER PERFORMANCE AND VOCABULARY MASTERY TOWARD LISTENING ABILITY AMONG SECOND GRADE STUDENTS OF MAN KRECEK PARE 2014-2015 - Afifah, Desi (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 5 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study aims to know how teacher performance is, studentsâ€™ vocabulary mastery is, and listening ability is, whether there is any simultaneous correlation and partially correlation among teacher performance and vocabulary mastery toward listening ability among the second grade students of MAN Krecek Pare Kediri. The design used was quantitative correlation research. It was conducted in MAN Krecek Pare Kediri at academic year 2014/2015. The population was 142 of second grade students of social class of MAN Krecek Pare Kediri and after calculated by using Sloven formula the sample taken was 105 students. Questionnaire and test were used to collect data. The data gotten was computed by partial correlation and regression and analyzed by SPSS version 16.0 to find descriptive, simultaneous and partial correlation. The results of the study were teacher performance belong to â€œfairâ€, the vocabulary mastery belong to â€œvery goodâ€ category, and listening ability belongs to â€œgoodâ€. Simultaneously, teacher performance and vocabulary mastery contributed 75.3% to listening ability. Partially, the correlation of teacher performance and vocabulary mastery toward listening ability is 0.758 and 0.801.